2013
DOI: 10.1007/s00425-013-1960-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative functional analysis of six drought-responsive promoters in transgenic rice

Abstract: Rice production is greatly affected by environmental stresses such as drought and high salinity. Transgenic rice plants tolerant to such stresses are expected to be produced. Stress-responsive promoters with low expression under normal growth conditions are needed to minimize the adverse effects of stress-tolerance genes on rice growth. We performed expression analyses of drought-responsive genes in rice plants using a microarray, and selected LIP9, OsNAC6, OsLEA14a, OsRAB16D, OsLEA3-1, and Oshox24 for promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…Stress-responsive Arabidopsis SNAC genes such as RD26 and ATAF1 , and rice SNAC genes such as SNAC1 , OsNAC6 / SNAC2 , and OsNAC5 can improve drought and/or high-salt stress tolerance when overexpressed (Tran et al, 2004; Hu et al, 2006; Nakashima et al, 2007; Takasaki et al, 2010; reviewed in Nakashima et al, 2012). Stress-responsive overexpression of NACs utilizing rice stress-responsive LIP9 , OsNAC6 , or OsHox24 promoters is effective in inducing stress tolerance without the inhibitory effects of NAC on plant growth (Nakashima et al, 2007, 2012, 2014; Takasaki et al, 2010). Recent studies have suggested that the root-specific promoter RCc3 is useful for the overexpression of SNACs such as SNAC1 and OsNAC10 to enhance the abiotic stress tolerance of rice in field conditions (Jeong et al, 2010, 2013; Redillas et al, 2012).…”
Section: Nac Tfs For Drought-responsive Gene Expression To Improve Drmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress-responsive Arabidopsis SNAC genes such as RD26 and ATAF1 , and rice SNAC genes such as SNAC1 , OsNAC6 / SNAC2 , and OsNAC5 can improve drought and/or high-salt stress tolerance when overexpressed (Tran et al, 2004; Hu et al, 2006; Nakashima et al, 2007; Takasaki et al, 2010; reviewed in Nakashima et al, 2012). Stress-responsive overexpression of NACs utilizing rice stress-responsive LIP9 , OsNAC6 , or OsHox24 promoters is effective in inducing stress tolerance without the inhibitory effects of NAC on plant growth (Nakashima et al, 2007, 2012, 2014; Takasaki et al, 2010). Recent studies have suggested that the root-specific promoter RCc3 is useful for the overexpression of SNACs such as SNAC1 and OsNAC10 to enhance the abiotic stress tolerance of rice in field conditions (Jeong et al, 2010, 2013; Redillas et al, 2012).…”
Section: Nac Tfs For Drought-responsive Gene Expression To Improve Drmentioning
confidence: 99%
“…These results indicate that SNACs have important roles in the control of abiotic stress responses and tolerance and that it is possible to improve stress tolerance by overexpressing SNACs using suitable promoters in the field. The many kinds of drought-responsive or tissue/organ-specific promoters reported for roots and stomata might be effective tools to control the expression of drought-responsive factors that cause growth defects at the right time and right position (Nakashima et al, 2007, 2014; Rai et al, 2009; Wu et al, 2009; Xiao et al, 2009; Yi et al, 2010; Ganguly et al, 2011; Yang and Xiong, 2011; Bang et al, 2013; Rusconi et al, 2013). …”
Section: Nac Tfs For Drought-responsive Gene Expression To Improve Drmentioning
confidence: 99%
“…Various studies have examined the role of promoters by fusing it with GUS reporter gene and subsequently analyzing the transgenic plants. 37,38 In this study, 1.5 kb upstream region from translation initiation site of OsSul1;1 was PCR amplified using oligonucleotide primers with digestion sites (Table S1), digested with restriction enzymes and cloned in binary vector pBI121 by replacing CaMV35S promoter (Fig. S3A and B).…”
mentioning
confidence: 99%
“…Comparative functional analysis of different stress responsive promoters in general and among different rice varieties has provided useful results which led to improved specificity and inducibility of stress responsive genes (Yi et al 2010;Nakashima et al 2014). Wsi18 promoter element, isolated from O. sativa cultivar Nakdong, was found to drive high levels of reporter GFP expression throughout the plant body, including flowers, with predominant activity in the whole grain on exposure of transgenic rice plants to drought and high salinity conditions (Yi et al 2011).…”
Section: Discussionmentioning
confidence: 99%